Impact of Corporate Culture on the Commitment to the Organization of Employees Working in Enterprises in the Mekong Delta, Vietnam (Journal of Pharmaceutical Negative Results, 2022)
In the context of increasingly clear competition between businesses today, building and promoting the positive effects of corporate culture to develop human resources as well as keep well-qualified employees is considered one of the priorities businesses should conduct. Research in businesses in the Mekong Delta provides evidence that several aspects of corporate culture have positive impacts on employee commitment to the organization. It means that these factors are predictive and can improve engagement.